S11 Improvement of Inspiratory Muscle and One Minute Sit to Stand function associated with Interstitial Lung Diseases pulmonary rehabilitation. (11th November 2022) - Alsomali, H; Chambers, F; McNeillie, L; Alquaimi, M; Donaldson, C; Langlands, L; Hartley, J; Harper, J; Bourke, AM; Ward, C; Forrest, I
Abstract : Introduction: Inspiratory Muscle Training (IMT) have shown benefit in terms of dyspnea, quality of life, and inspiratory muscle function in patients with COPD, studies evaluating its effectiveness and role in patients with Interstitial Lung Diseases (ILD) are scant. This study aimed to evaluate the feasibility and effectiveness of IMT as part of a pulmonary rehabilitation program in patients with ILD. Methods: A feasibility study with a randomized controlled trial design. Patients with the diagnosis of ILD were randomized to either an intervention group receiving IMT with POWERBreathe® and 8 weeks of pulmonary rehabilitation program, or to a control group receiving pulmonary rehabilitation program only. The pulmonary rehabilitation program consisted of Exercise training and education sessions. The exercise training included warming up, aerobic exercises, strength training, and cooling down. Twice a week home exercises and 4 days/week walking were also prescribed. Maximum Inspiratory Pressure (MIP), One Minute Sit to Stand Test (1MSTS), The King's Brief Interstitial Lung Disease Questionnaire (K-BILD), and Fatigue Severity Scale (FSS) data were collected. Results: A total of 14 participants with ILD, 64% male with mean (SD) age 68 years (9.39) were enrolled into this study. The pulmonary rehabilitation program had an attendance and completion rates of 86.81% and 81.82% respectively. No adverse events have been recorded. The MIP improved in all participants in the intervention and the control group. Preliminary data analysis with Mann-Whitney test indicated that there was no statistically significant difference between the intervention and control group in MIP after 8 weeks. The MIP of intervention group median (Mdn=85.7) was higher than that of the control group (Mdn=67.35), p=0.714. The 1MSTS improved in (2 out 3) and (6 out 6) in the intervention and control group respectively. A statistically significant improvement was found between pre and post 1MSTS in the control group with a median difference of (Mdn=3.5), p=0.03.There were no statistically significant difference in K-BILD and FSS. Conclusion: Pulmonary rehabilitation for patients with ILD is feasible and is associated with improved maximal inspiratory pressure and functional exercise capacity immediately after pulmonary rehabilitation program with no adverse events.